A REVIEW OF TPACK AND SAMR MODELS: HOW SHOULD LANGUAGE TEACHERS ADOPT TECHNOLOGY? - Justsinta Sindi Alivi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This paper primarily aims at reviewing the idea of Technological Pedagogical and Content Knowledge (TPACK) as well as the application of Substitution, Augmentation, Modification, and Redefinition (SAMR) frameworks in teaching practices. In particular, this paper is expected to provide insight for language teachers interested in Information and Communication Technology (ICT) incorporation to teaching as regards TPACK and SAMR understanding. Accordingly, the language teachers are expected to be able to incorporate technology into teaching in appropriate ways reflecting to the frameworks. Further, description about how TPACK and SAMR carried out in teaching is presented to provide teachers with a clear definition of the frameworks. Additionally, some views concerning challenges of the application are also discussed as an evaluation.